2008
DOI: 10.1007/s00497-008-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Histological comparison between wheat embryos developing in vitro from isolated zygotes and those developing in vivo

Abstract: There is currently great interest shown in understanding the process of embryogenesis and, due to the relative inaccessibility of these structures in planta, extended studies are carried out in various in vitro systems. The culture of isolated zygotes in particular provides an excellent platform to study the process of in planta embryogenesis. However, very few comparisons have been made between zygotic embryos grown entirely in cultures and those grown in vivo. The present study analyses the differences and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
1
4
0
Order By: Relevance
“…The similar observation for abundant starch and protein accumulation was found in the scutellum of hexaploid wheat embryos developing in vitro from isolated zygotes [52]. In agreement with this, the “dormant” structures formed in the presence of DAM showed visual similarity with scutellum of zygotic embryos being hard, white and non translucent.…”
Section: Discussionsupporting
confidence: 81%
“…The similar observation for abundant starch and protein accumulation was found in the scutellum of hexaploid wheat embryos developing in vitro from isolated zygotes [52]. In agreement with this, the “dormant” structures formed in the presence of DAM showed visual similarity with scutellum of zygotic embryos being hard, white and non translucent.…”
Section: Discussionsupporting
confidence: 81%
“…A slight cellular disorganization, limited mitotic activity, intercellular spaces, and a moderate degree of vacuolization can be observed. Bakos et al (2009), who have also observed similar characteristics in embryos of Triticum aestivum obtained in vitro, have considered these characteristics as a discrete dysfunction typical of the in vitro environment that does not compromise the conversion of plants, as found in P. aduncum. On the other hand, somatic embryos with partially organized stem meristem, with differentiated cells with large vacuoles and small nuclei, as reported in Vitis vinifera (Goebel-Tourand et al 1993), or with limited or absent meristematic activity and presence of vacuolated cells, as reported in Ipomoea potatoes (Padmanabhan et al 1998), presented problematic conversion.…”
Section: Germination Of Somatic Embryos and Acclimatization Ofmentioning
confidence: 83%
“…Considerable amounts of starch have also been seen in in vitro embryos of Dendrocalamus hamiltonii (Godbole et al 2004) and T. aestivum (Bakos et al 2009). In contrast, several other authors have not identified significant amounts of starch grains in somatic embryos at different stages of development, and their consumption was attributed to the formation of embryogenic structures.…”
Section: Germination Of Somatic Embryos and Acclimatization Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…The in vitro culture of ovules a few hours after pollination [400] or isolated zygotes [401] provides an excellent system to study embryogenesis, as this process is more complex to analyze in plants. Therefore, in vitro investigations during embryo development have already been established in maize [402,403], barley [404], wheat [401,[404][405][406][407][408], rice [409][410][411][412], tobacco [413], and Setaria viridis [414]. The use of histological and other microscopic tools is simplified during in vitro culture.…”
Section: Analysis Of Embryogenesis With Embryo Rescue Technical Holdermentioning
confidence: 99%